THE INFLUENCE OF INFLUENCE MARKETING, PRODUCT VARIATION, AND TRUST ON WOMEN’S CLOTHING PURCHASE DECISIONS ON TIKTOK - Rahmat Hidayat; Fanny Wulanda; Yuda Anggi Pratama (Ikatan Dosen Menulis, 2026)
This study aims to determine the influence of influencer marketing, product variety, and trust on purchasing decisions for women's clothing in TikTok Shop. This study uses a quantitative approach with the positivism method. The number of samples in this study was 87 respondents, with data collected through a Likert scale-based questionnaire. The results of the analysis show that the influencer marketing variable has a positive and significant effect on purchasing decisions for women's clothing in TikTok Shop, with a significance value of 0.001 <0.05. The product variety variable has a positive and significant effect on purchasing decisions for women's clothing in TikTok Shop, with a significance value of 0.000 <0.05. The trust variable has no effect on purchasing decisions for women's clothing in TikTok Shop, with a significance value of 0.738 > 0.05. And the results of the multiple linear regression produced are Y = 10.871 + 0.604 X1 + 0.622 X2 + -0.53 X3 + e. The coefficient of determination is 64.7%, while the remaining 35.3% is explained by other variables.